Exploring Innovation Management Strategies in Pakistan’s Manufacturing Industry - Irfanullah Khan; Sikandar Bilal Khattak; Fawad Ahmad (Spectrum of Engineering Sciences, 2024)
The focus of this research is to identify emergent factors that determine the management of innovation in manufacturing companies in Pakistan. I continue the study emphasizing on the rising significance of innovation to manufacturing firms in emerging economy where competitive forces, legal demands and the necessity for technological upgrades become central to growth. The comparatively low amount of research focusing on the field of innovation management practices existing within the Pakistani manufacturing industry, stressing the importance of developing insights on these practices in order to promote competitiveness. The first objective of this research is to explore and evaluate factors influencing the manufacturing industry in Pakistan, engaging stakeholders, and the efficiency of the multiple strategies in innovation. Besides, through survey, the perceived importance and involvement in innovation activities of the stakeholders of the industries were identified and measured. The Leadership Commitment, Technological Infrastructure, and Employee Training were used because they aimed at evaluating the support of the company for innovation activities. Academic sources, self-administered survey, RII, AHP, SPSS, PESTEL Analysis are used in this study to analyze survey data which gives great mileage in its assessment of the factors that affect innovation success. The study finally provides recommendations which play the key importance is that the professional management of innovation requires a holistic approach in Pakistan’s manufacturing industry. A management support, resource availability and continuous enhancement approach is suggested to work on internal endowments and external forces. This study is useful for policymakers and industry stakeholders because it advises that enhancement of areas of competitive advantage and targeted support and resource should be given focus in order to nurture the culture of innovation and sustainable growth of the manufacturing industry of Pakistan. Keywords: Pakistani Manufacturing Industry, key Factors, Relative Importance Index (RII), Analytic Hierarchy Process (AHP), PESTEL Analysis